Strategi CAKEP dalam Pendampingan Pelaksanaan Kurikulum Merdeka di SBLN 1 Sungai Pagu - Hayati, Leni Murni; Nanda, Dendy H; Prasetia, Agung Tri (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to analyze the impact of the CAKEP strategy implementation in assisting the Merdeka Curriculum implementation at SLB N 1 Sungai Pagu. The CAKEP strategy, comprising five main components: Coaching, Execution Arrangement, Collaboration, Expert Involvement, and Limitless Care, was applied to enhance inclusive education quality for students with special needs. The results indicate that this approach effectively improved teacher competence, parent involvement, and community support in creating a more conducive learning environment. Increased teacher motivation, optimized resource utilization, and external support from psychologists and community leaders significantly enhanced the curriculum’s effectiveness. These findings highlight the importance of cross-sector partnerships in inclusive education and offer a potential model for other resource-limited schools.